MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN TRADISIONAL KUCING TIKUS PADA ANAK KELOMPOK B DI TK AT-TAUBAH JL.HARAPAN PEKANBARU - Luvi Yonanta; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations made on group B children in At-taubah Kindergarten related to gross motor skills still need stimulation due to lack of awareness of the importance of developing gross motor skills in children, so students do not run seriously, children are less respond to the game given by the teacher. The purpose of this study was to investigate efforts to improve gross motor skills of Group B children at At-taubah Kindergarten through cat rat games. The population is limited by the number of subjects or individuals who have at least the same nature. The population in this study was group B of At-taubah Kindergarten with a total of 12 people. Consisting of male students 6 and female students 6. Samples used in this study amounted to 12 people, the data collection method is total sampling. The data analysis technique used in this study is quantitative and qualitative descriptive analysis. Quantitative descriptions are used to analyze data in the form of numbers. Increased gross motor skills can be said to be optimal based on the results of observational data and documentation obtained in each cycle. It can be seen that the initial condition of the child before the action shows gross motor skills in children shows that only 3 (25%) of the total number of children, in the first cycle increased to 6 (50%) of the total number of children and in the second cycle increased to reach 10 (83.33%) thus shows that children's gross motor skills have improved very well. The indicator of running in pre-action is only 1 (8.33%) of the number of children who succeed, in the first cycle increased to 8 (66.67%) and in the second cycle increased to 10 (83.33%) this data shows that the ability gross motor children have reached good criteria. The catch indicator in pre-action was only 2 (16.67%) of the total number of children, in cycle I it increased to 3 (25%) of the number of children and cycle II increased to 9 (75%) of the total number of children indicating that gross motor skills the capture indicator has reached good criteria.Key Words: Gross Motor Skills, Cat Rat Games